Utilisation of Multiple Languages in Teaching and Learning: Mapping Initiatives at the University of South Africa (Unisa) (London Journal of Research In Humanities and Social Sciences, 2024)
In South Africa, the role of language is crucial in transforming higher education because it not only affects academic access and success, but also affirms diversity. This means that the implementation of multilingual policies at South African universities constitutes a paradigm shift from the prejudiced methods of the old apartheid regime. Central to the University of South Africa’s 2030 strategic plan is the need to transform teaching and learning as well as research and community engagement in order for the university to operate/ function effectively as a leading Open Distance e-Learning (ODeL) institution.  Besides the decolonisation of the curriculum, the transformation of teaching and learning requires a review of how most students learn. In various South African legislative reports on language issues, a common problem is that language continues to be a barrier to access and success in higher education. The purpose of this research paper therefore is to map the practices that the university has initiated to overcome the language barrier by creating a space for the previously marginalised indigenous languages to be used in teaching and learning. The study utilises a qualitative approach in examining the processes, and challenges of implementing the initiatives to assist students in their learning. It is hoped that the recommendations made will promote collaborative programmes among institutions of higher learning in developing and strengthening the use of multiple languages in teaching and learning. The current study does not examine the impact of these initiatives on the success and pass rate of students, so further research on this subject is needed.
Keywords: The Space The Existence Basic Energy Intellectual Energy The Time The Energy The Information Matter Cosmic origin; Teaching and Learning; translation; indigenous languages; language policy; African languages; Language of Learning and Teaching (LoLT); multilingualism